2019
DOI: 10.1182/blood-2018-09-874529
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 mutations reduce binding of NOTCH1, leading to cleaved NOTCH1 accumulation and target gene activation in CLL

Abstract: NOTCH1 is mutated in 10% of chronic lymphocytic leukemia (CLL) patients and is associated with poor outcome. However, NOTCH1 activation is identified in approximately one-half of CLL cases even in the absence of NOTCH1 mutations. Hence, there appear to be additional factors responsible for the impairment of NOTCH1 degradation. E3-ubiquitin ligase F-box and WD40 repeat domain containing-7 (FBXW7), a negative regulator of NOTCH1, is mutated in 2% to 6% of CLL patients. The functional consequences of these mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…MYC and NOTCH1 as well as common interactor FBXW7 expression levels were significantly altered in several cancers, especially in blood cancers [67]. Consistent with the results, mutations in FBXW7 were reported in 2-6% of chronic lymphocytic leukemia (CLL) resulting in the activation of NOTCH11 intracellular domain (NCID) and MYC target genes [68]. Network visualization also revealed that RELA, GSK3B…”
Section: Case 4 Application Of Pic-venn For Elucidation Of Signal Trsupporting
confidence: 75%
“…MYC and NOTCH1 as well as common interactor FBXW7 expression levels were significantly altered in several cancers, especially in blood cancers [67]. Consistent with the results, mutations in FBXW7 were reported in 2-6% of chronic lymphocytic leukemia (CLL) resulting in the activation of NOTCH11 intracellular domain (NCID) and MYC target genes [68]. Network visualization also revealed that RELA, GSK3B…”
Section: Case 4 Application Of Pic-venn For Elucidation Of Signal Trsupporting
confidence: 75%
“…A previous study identified FBW7 mutations in 36 out of 905 untreated patients with CLL. All these mutations are heterozygous, missense in 78% of cases and primarily affect the substrate-binding domain of WD40 (77). Furthermore, 10% of the mutations were located on the first exon of the α-transcript.…”
Section: Chronic Lymphocytic Leukemia (Cll)mentioning
confidence: 99%
“…Furthermore, 10% of the mutations were located on the first exon of the α-transcript. In order to identify the target protein of FBW7 in CLL, a WD40 domain-truncated CLL cell line (HG-3) was generated using the CRISPR/Case9 method (77). Homozygous truncation of FBW7 results in increased levels of activated Notch1-NICD and c-Myc proteins, and in enhanced activity of HIF1-α (77).…”
Section: Chronic Lymphocytic Leukemia (Cll)mentioning
confidence: 99%
See 2 more Smart Citations